1991
DOI: 10.1111/j.1476-5381.1991.tb12383.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin activates tachykinin release from capsaicin‐sensitive afferents in guinea‐pig bronchi through a ruthenium red‐sensitive pathway

Abstract: 1 We have investigated the ability of prostacyclin (PGO2) to contract guinea-pig isolated bronchi and the possible involvement of capsaicin-sensitive primary afferents in the response to PG12 . 2 PGO2 (0.1-100pUM) produced concentration-dependent contractions of the guinea-pig isolated bronchi. In vitro capsaicin desensitization (10pM for 30min followed by washing) significantly reduced the PG12-induced contraction at all concentrations tested. A capsaicin-resistant component of contraction (40-60% of the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In contrast, both bradykinin and prostanoids have been shown to evoke neuropeptide release from sensory nerve terminals in various peripheral tissues (Amann et al, 1989;Franco-Cereceda et al, 1989;Geppetti et al, 1990a,b;1991;Mapp et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both bradykinin and prostanoids have been shown to evoke neuropeptide release from sensory nerve terminals in various peripheral tissues (Amann et al, 1989;Franco-Cereceda et al, 1989;Geppetti et al, 1990a,b;1991;Mapp et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the atrioventricular fistula model of heart failure, there are increased levels of PGI2 in the pericardial effusate.39 Since the model we used has been characterized histologically as being consistent with chronic ischemia,40 there may be several substances that are released by the myocardium that potentiate the response to PGI2, such as potassium and bradykinin 35,41. In an important study byMapp et al,42 it was shown that the ability of PGI2 to contract guinea pig isolated bronchi was mediated by capsaicin-sensitive afferents. A selective inhibitor of NK-2-tachykinin receptors decreased the PGI2 contractions.…”
mentioning
confidence: 97%
“…Therefore, endogenous prostaglandins may potentiate the response of asthmatic airway nerves to inhaled NKA, and only part of the effects of NKA may result from the direct release of contractile prostaglandins. On the other hand, cyclooxygenase products activate tachykinin release from capsaicin-sensitive afferents in guinea-pig airways [33], and stimulate both pulmonary and bronchial C fibres in dogs [34]. Other possible explanations for the L-ASA reduction in NKA responsiveness in asthma may include down regulation of NK receptors, and modulation of postreceptor events coupled to NKA-mediated contraction of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%